Successful professional reviews for civil engineers - Waterhouse, Patrick (Civil engineer) (ICE Publishing, 2022)
'Successful Professional Reviews for Civil Engineers' provides a comprehensive guide to the constituent parts of the ICE Professional Review process, ideal for those engineers nearing the completion of their initial professional development. Working logically through the review process for incorporated and chartered civil engineers, the chapters ensure that the candidate is provided with an in-depth understanding of the criteria used in the assessment and how best to demonstrate these. Fully updated, this fifth edition details how any candidate, from any background, might demonstrate the attributes sought by reviewers. It offers many suggestions, examples and anecdotes to assist and guide each individual towards a successful review.